Does China’s housing supply-demand relationship impact urban innovation capability - Zhang, Juanfeng; Hao, Ning; Zhao, Guochao; Li, Lele; Xiang, Xiaoyi; Han, Rui (International Journal of Strategic Property Management, 2025)
Unlike existing literature that explores the impact of house prices on urban innovation, this paper skillfully examines the relationship between the housing market and urban innovation from the perspective of the housing supply-demand (S-D) relationship. Utilizing panel data from 284 prefecture-level cities in China spanning from 2005 to 2020, this study investigates the respective impacts of housing supply, housing demand, and their interplay on urban innovation capacity (UIC). Our findings indicate that housing supply positively influences UIC, with a coefficient of 0.060; specifically, for every 1% increase in housing supply, UIC increases by 0.06%. Similarly, housing demand also significantly affects UIC, with a coefficient of 0.060, suggesting that a 1% increase in housing demand corresponds to a 0.060% rise in UIC. However, we observe a significant negative effect of the housing S-D relationship on UIC, with a coefficient of –0.049, indicating that an increase in the housing S-D ratio detrimentally impacts urban innovation. Furthermore, our analysis reveals that as the housing supply-demand ratio rises, house prices also tend to increase. Additionally, we identify heterogeneity in our results, indicating variations in the housing supply-demand ratio’s impact on the innovation capacity of cities across different regions.